Accurate targeted long-read DNA methylation and hydroxymethylation sequencing with TAPS - Liu, Y; Cheng, J; Siejka-Zielinska, P; Weldon, C; Roberts, H; Lopopolo, M; Magri, A; D'Arienzo, V; Harris, JM; McKeating, J; Song, C (BMC, 2020)
We present long-read Tet-assisted pyridine borane sequencing (lrTAPS) for targeted base-resolution sequencing of DNA methylation and hydroxymethylation in regions up to 10 kb from nanogram-level input. Compatible with both Oxford Nanopore and PacBio Single-Molecule Real-Time (SMRT) sequencing, lrTAPS detects methylation with accuracy comparable to short-read Illumina sequencing but with long-range epigenetic phasing. We applied lrTAPS to sequence difficult-to-map regions in mouse embryonic stem cells and to identify distinct methylation events in the integrated hepatitis B virus genome.